REFORMS IN THE FIELD OF TOURISM IN UZBEKISTAN AND THEIR GEOGRAPHICAL ASPECTS (Scientific journal of the Fergana State University, 2026)
This article discusses the issues of tourism development in our country, the impact of tourism on the economy, the theories of foreign scientists on tourism, the reforms being carried out in the tourism sector in our republic, foreign tourists visiting Uzbekistan, foreign tourists by country, tourist visits, tourist information, as well as tasks and measures to be implemented to increase the role and place of tourism in further increasing the potential of our economy. Also, the impact of tourism on the economy is not limited to hotels and restaurants, but also covers broader infrastructure projects, public services, trade and transport sectors, and the acceleration of globalization processes taking place in the world requires countries to create opportunities to solve important issues through the development of the tourism industry. The unique nature of our country, national reserves, and mountainous regions have great potential for the development of tourism. In particular, the development of medical tourism, pilgrimage tourism and ecotourism will give a great impetus not only to the development of the economy, but also to the development of social sectors. Today, in the scientific research of developed countries, a number of scientific studies are being conducted to study the impact of the tourism sector on their economy, social sphere, ecology and other areas. In recent years, due to the reforms carried out in the tourism sector in our republic, the number of foreign tourists visiting our country has been increasing year by year. Foreign tourist arrivals in Uzbekistan are a country with a rich historical and cultural heritage, and its tourism sector has been developing rapidly in recent years, making extensive use of our existing opportunities in the development of tourism in our country and applying foreign experience in practice, planning and modernizing road infrastructure taking into account the needs of the local population and tourists, will increase the tourist activity of the country's citizens and lead to an increase in the flow of foreign tourists.